Development of fragility curves for seismic vulnerability assessment: The case of Philippine General Hospital spine building - Michael B. Baylon; Maria Emilia P. Sevilla; Miller DL. Cutora; Rikki Mae S. Villa; Princess Mherlene P. Reynes; Jhona May V. Montemayor (International Research Journal of Science, Technology, Education, and Management, 2022)
The Philippine General Hospital (PGH) is a tertiary hospital in Ermita, Manila, that was founded on August 17, 1907. It adheres to the philosophy of providing all Filipinos with internationally competitive, cost-effective, compassionate, and accessible health care. It was recently one of the COVID-19 facilities. The PGH sits 9.2 kilometers east of the West Valley Fault, making it more vulnerable to 'The Big One,' a 7.2 magnitude earthquake. Until present, no research has been done to examine the PGH's seismic susceptibility in the case of a large-magnitude earthquake. In keeping with this, the study intended to analyze the seismic susceptibility of the Spine Building, one of PGH's oldest structures. It focused on constructing fragility curves to assess if the building could sustain a 0.4g peak ground acceleration (PGA) earthquake with a maximum likelihood of exceedance of 10%, as required by the Philippine National Structural Code (NSCP) for Seismic Zone 4 sites. The study employed 12 worldwide and 12 local earthquakes from the Incorporated Research Institutions for Seismology, with PGA excitation levels ranging from 0.1g to 3.0g (with a 0.1g gap) (IRIS). The structural model of the PGH Spine Building was created using SAP2000, which was subsequently utilized to perform Pushover Analysis using the Capacity Spectrum Method (CSM). The PGH Spine Building might collapse with 0.538g PGA, which corresponds to Intensity VIII, according to the results of the developed fragility curves, producing significant structural shaking. Furthermore, for 0.4g PGA, the calculated highest likelihood of exceedance in the 'collapse damage' condition was 5.24 percent, with no results above 10%, implying that the PGH Spine Building complies with the NSCP seismic requirement for structures located in Seismic Zone 4. As a result, an adequate retrofitting strategy is not required for the PGH Spine Building.